2021
DOI: 10.1016/j.ejmp.2021.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the dose in bone for spine stereotactic body radiotherapy

Abstract: Current quality assurance of radiotherapy involving bony regions generally utilises homogeneous phantoms and dose calculations, ignoring the challenges of heterogeneities with dosimetry problems likely occurring around bone. Anthropomorphic phantoms with synthetic bony materials enable realistic end-to-end testing in clinical scenarios. This work reports on measurements and calculated corrections required to directly report dose in bony materials in the context of comprehensive end-to-end dosimetry audit measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
3
4
0
Order By: Relevance
“…This dependency was also stressed in previous studies (Delbaere et al 2019, Younes et al 2021) where differences up to 2.6% were found between the absorbed dose D m m calculated in the Gammex cortical bone and in the ICRP-23 (ICRP 1975) cortical bone. The same findings could be observed on the ] factors and could explain the difference between our film correction factor in the Gammex cortical bone (∼0.934) and the one calculated by Shaw et al (2021) in the CIRS (Norfolk, VA, USA) cortical bone (∼0.875). In the case of equivalent lung media, the correction factors in the CIRS lung calculated by Shaw et al (2023) were in agreement with our values in the Gammex lung (∼0.970-0.980) but were not consistent with Charles et al (2021) who found a factor equal to unity for the ICRU-44 lung (ICRU 1989).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This dependency was also stressed in previous studies (Delbaere et al 2019, Younes et al 2021) where differences up to 2.6% were found between the absorbed dose D m m calculated in the Gammex cortical bone and in the ICRP-23 (ICRP 1975) cortical bone. The same findings could be observed on the ] factors and could explain the difference between our film correction factor in the Gammex cortical bone (∼0.934) and the one calculated by Shaw et al (2021) in the CIRS (Norfolk, VA, USA) cortical bone (∼0.875). In the case of equivalent lung media, the correction factors in the CIRS lung calculated by Shaw et al (2023) were in agreement with our values in the Gammex lung (∼0.970-0.980) but were not consistent with Charles et al (2021) who found a factor equal to unity for the ICRU-44 lung (ICRU 1989).…”
Section: Discussionsupporting
confidence: 87%
“…The cross-calibration coefficients were established using an aluminium-core calorimeter embedded in an aluminium phantom. Surprisingly, the authors pointed out that their film results were close to those reported by Shaw et al (2021) in the CIRS cortical bone. Nevertheless, their corrections are closer to our value in Teflon (∼0.866) than in the Gammex cortical bone.…”
Section: Discussionsupporting
confidence: 69%
“…• Trial credentialling (47%) • Australian Clinical Dosimetry Service (ACDS) SABR dosimetry audit 37 (35%)…”
Section: Discussionmentioning
confidence: 99%
“…Since the film dosimetry protocol followed yields dose to water within the medium where the films lay (i.e., bone and air), 20 appropriate correction factors were calculated to convert this to corresponding dose to medium values, according to 20 : Kmedbadbreak=0.28emDmedDfilmLGKDfilmDwCal$$\begin{equation}{K_{med}} = \;{\left( {\frac{{{D_{med}}}}{{{D_{film}}}}} \right)^{LGK}}{\left( {\frac{{{D_{film}}}}{{{D_w}}}} \right)^{Cal}}\end{equation}$$where, ()DmedDfilmLGK${\left( {\frac{{{D_{med}}}}{{{D_{film}}}}}\right)^{LGK}}$is the ratio of dose to medium to dose to film for the LGK photon fields and irradiation geometries and0.28emDfilmDwCal${\rm{\;}}{\left( {\frac{{{D_{film}}}}{{{D_w}}}} \right)^{Cal}}$ is the ratio of dose to film to dose to water for the film calibration photon field (i.e., the 60 Co gamma ray reference field) and calibration geometries (see also Section 2.5).…”
Section: Methodsmentioning
confidence: 99%
“…In-house software routines developed in MATLAB ® (The MathWorks, Inc., Natick, MA) were used to read the measured pixel values of each experimental film piece and convert them into dose values using a triple channel technique and the calibration data of the used film batch. 19 Since the film dosimetry protocol followed yields dose to water within the medium where the films lay (i.e., bone and air), 20 appropriate correction factors were calculated to convert this to corresponding dose to medium values, according to 20 :…”
Section: Experimental Measurementsmentioning
confidence: 99%